2018
DOI: 10.3844/ajbbsp.2018.108.116
|View full text |Cite
|
Sign up to set email alerts
|

Current Laboratory Biosecurity for Handling Pathogenic Viruses

Abstract: Abstract:The recent emergence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…161 The importance of biosecurity systems to prevent loss, theft, misuse, diversion, or intentional unauthorised release of pathogenic viruses handled in the laboratory has previously been described. 163 For PCR detection of pathogenic viruses, the genetic material is first extracted, isolated and purified. EV-A71 RNA extraction is commonly carried out using commercial kits.…”
Section: Molecular Mechanism Of Enterovirus A71 Infection and Innate ...mentioning
confidence: 99%
See 1 more Smart Citation
“…161 The importance of biosecurity systems to prevent loss, theft, misuse, diversion, or intentional unauthorised release of pathogenic viruses handled in the laboratory has previously been described. 163 For PCR detection of pathogenic viruses, the genetic material is first extracted, isolated and purified. EV-A71 RNA extraction is commonly carried out using commercial kits.…”
Section: Molecular Mechanism Of Enterovirus A71 Infection and Innate ...mentioning
confidence: 99%
“…All manipulation of infectious viral specimen material and suspensions must be performed inside a functional class II biological safety cabinet 161 . The importance of biosecurity systems to prevent loss, theft, misuse, diversion, or intentional unauthorised release of pathogenic viruses handled in the laboratory has previously been described 163 …”
Section: Molecular Detection and Characterisation Of Enterovirus A71mentioning
confidence: 99%
“…Indeed, with the current advanced powerful genetic engineering techniques, a virus can be modified, redesigned, reconstructed or even synthesized. This can potentially bring about a novel virus which is unprecedented in nature ( Artika and Ma'roef, 2018 ). The molecular characteristics of the SARS-CoV-2 indicated that the virus is not a product of purposeful manipulation.…”
Section: Molecular Characteristics Of Sars-cov-2mentioning
confidence: 99%
“…To address the possibility that pathogenic viruses may be misused for malicious purposes, implementation of a biosecurity system in any laboratory working with pathogenic viruses is recommended. The laboratory biosecurity system should cover physical security, virus control and accountability, personnel security, transport security, and information security; the implementation of which needs to be integrated with the overall biosafety plan (Artika and Ma'roef, 2018).…”
Section: Development Of Laboratory Capacitymentioning
confidence: 99%